2010
DOI: 10.1088/0004-637x/723/2/1139
|View full text |Cite
|
Sign up to set email alerts
|

COJ= 1-0 SPECTROSCOPY OF FOUR SUBMILLIMETER GALAXIES WITH THE ZPECTROMETER ON THE GREEN BANK TELESCOPE

Abstract: We report detections of three z ∼ 2.5 submillimeter-selected galaxies (SMGs; SMM J14011+0252, SMM J14009+0252, SMM J04431+0210) in the lowest rotational transition of the carbon monoxide molecule (CO J = 1 − 0) and one nondetection (SMM J04433+0210). For the three galaxies we detected, we find a line-integrated brightness temperature ratio of the J = 3 − 2 and 1 − 0 lines of 0.68±0.08; the 1−0 line is stronger than predicted by the frequent assumption of equal brightnesses in the two lines and by most single-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
140
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(171 citation statements)
references
References 63 publications
27
140
4
Order By: Relevance
“…The individual stellar masses from the system are each > 10 11 M , while the galaxy is among the brightest CO emitters known to date. The baryonic gas fraction of the galaxy is ∼ 50%, even (Riechers et al, 2011c;Ivison et al, 2011;Harris et al, 2010;Carilli et al, 2010) and the small blue squares are mostly SMGs with higher-J CO line measurements converted to CO(1-0) using the mean observed ratios (Bothwell et al, 2013a;). The red line shows the best-fit relation for unlensed SMGs from Bothwell et al (2013a), see also Harris et al (2012).…”
Section: Environments Of Dsfgsmentioning
confidence: 99%
See 2 more Smart Citations
“…The individual stellar masses from the system are each > 10 11 M , while the galaxy is among the brightest CO emitters known to date. The baryonic gas fraction of the galaxy is ∼ 50%, even (Riechers et al, 2011c;Ivison et al, 2011;Harris et al, 2010;Carilli et al, 2010) and the small blue squares are mostly SMGs with higher-J CO line measurements converted to CO(1-0) using the mean observed ratios (Bothwell et al, 2013a;). The red line shows the best-fit relation for unlensed SMGs from Bothwell et al (2013a), see also Harris et al (2012).…”
Section: Environments Of Dsfgsmentioning
confidence: 99%
“…However, early detections of CO (J=1-0) with the Green Bank Telescope (GBT) and VLA revealed that SMGs appear to exhibit a diverse range of CO SLEDs, and that at least some SMGs may indeed contain large volumes of sub-thermally excited gas (e.g. Greve et al, 2003;Hainline et al, 2006;Carilli et al, 2010;Harris et al, 2010;Ivison et al, 2011). Still, other SMGs show rather extreme conditions, and appear to have thermalized level populations through the J=6-5 transition (e.g.…”
Section: Co Excitation and Spectral Line Energy Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, weak extended emission seems like an unlikely cause of the discrepancy between the interferometric and single-dish fluxes, and some other origin is likely given its redshift discrepancy (discussed previously). In the subsequent analysis of the r 3,1 distributions, we consider the distributions both with and without the peculiar r 3,1 measurements, as well as the 16 We also note that the flux scales assumed for the original Harris et al (2010) GBT measurements differ from the Perley-Butler 2013 standards used in the VLA pipeline. However, the assumed calibration fluxes for 3C286 and 3C48 are larger for the VLA observations than for the GBT observations (by as much as~10%), making the flux calibration issues an unlikely sourceof our measured flux discrepancies.…”
Section: Peculiar R 31 Values and Comparisons To Previous Measurementsmentioning
confidence: 99%
“…The relatively recent availability of Ka-band receivers on the Karl G. Jansky Very Large Array (VLA) and the Robert C. Byrd Green Bank Telescope (GBT) has led to a small but growing number of CO detections inz 2-3 galaxies that are complete down to the lowest rotational line, CO(1-0), which is crucial for tracing the coldest gas components (e.g., Harris et al 2010Harris et al , 2012Swinbank et al 2010;Danielson et al 2011;Ivison et al 2011Ivison et al , 2012Ivison et al , 2013Riechers et al 2011bRiechers et al , 2011cRiechers et al , 2011dThomson et al 2012Thomson et al , 2015Fu et al 2013;Sharon et al 2013Sharon et al , 2015; for CO(1-0) detections at other redshifts using other bands, see Carilli et al 2002;Greve et al 2003;Hainline et al 2006;Riechers et al 2006Riechers et al , 2009Riechers et al , 2011dRiechers et al , 2013Dannerbauer et al 2009;Aravena et al 2010Aravena et al , 2014Aravena et al , 2016Carilli et al 2010;Emonts et al 2011). , indicative of a multiphase molecular ISM including a previously unaccounted for cold gas reservoir (e.g., Harris et al 2010;Swinbank et al 2010;Danielson et al 2011;Ivison et al 2011;Thomson et al 2012;Bothwell et al 2013; see Riechers et al 2011c;Sharon et al 2013Sharon et al , 2015. In contrast, AGN host galaxies at ...…”
Section: Introductionmentioning
confidence: 99%